PROMOSI KESEHATAN PROMOSI KESEHATAN MELALUI MEDIA SOSIAL INSTAGRAM SEBAGAI SARANA EDUKASI - Olga Jadha Casmira; Bagus Widjanarko; Ani Margawati (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2022)
Abstract How to present and convey information can be through various media, but to determine which media is more effective, one that touches or deals directly with the community is Instagram. Instagram social media shows that creatively packaged photo communication is an important factor in attracting attention. The Instagram social media application that contains photos/images and can be shared is proven to have a strong correlation in influencing interest. This study aims to see the effect of health promotion through social media Instagram as a means of education. In connection with this, the researcher wanted to see if Instagram showed any influence in health promotion through social media.. The efforts made by researchers recommend that Instagram be used as a medium for discussion and education, as well as a medium for influencing and making policies. Keywords: Promotion, Social Media Instagram, Education